Calibration Factor for Conventional Linear Cephalometric Measurements - Ruba J. Mohammed; Dr. Nazar Gh. Jameel; Mohammad N Al-Mallah (University of Mosul, College of Dentistry, 2018)
Abstract Aims: the aim of this study is to determine a calibration factor to eliminate the distortion in the linear cephalometric measurements. Materials and Methods; the study was performed on the 5 dry skulls, the first skull contained 12 radiopaque markers fixed at different plains, and radiographed by digital cephalometric x-ray machine. The X and Y axes of the shadow of each radiopaque marker used to estimate the calibration factor. Eight linear distances measured directly and radiographically on the conventional cephalographs of the 5 skulls to evaluate the detected calibration factor. Results; the results showed no-significant difference (p > 0.05) between the direct and calibrated radiographic measurement on the digital and conventional cephalographs. whereas significant difference was found between the conventional cephalometric linear measurements as compared with direct anatomical linear and the conventional cephalometric linear measurements with those measurements manipulated with the estimated calibration factor (p < 0.05). Conclusions; this study found that the conventional cephalometric linear measurements could be reliable as that of digital cephalometric linear measurements, if it's calibrated by the calibration factor (1.08) which is estimated by the present study.